Mensagem do Comandante da EsAO - Revista Giro do Horizonte (Giro do Horizonte, 2022)
<h3 class="media-heading" style="box-sizing: border-box; font-family: Verdana, Arial, Helvetica, sans-serif; font-weight: 400; line-height: 1.1; color: #333333; margin-top: 0px; margin-bottom: 5px; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Mensagem do Comandante da EsAO